The State Responsibility Developments for Climate Change Damage: A Comparative Study - Mahran , Islam Mahmoud (Journal of Ecohumanism, 2024)
The phenomenon of climate change is one of the most important issues discussed on the international and national scene as it represents a challenge facing humanity. Legal interest in the phenomenon of climate change began at the level of international organization in 1992 through the United Nations Framework Convention on Climate Change, then legal interest took the direction of obligation through the advanced judiciary of national courts in some countries and the rulings issued by them that gave this contemporary law the characteristic of obligation. The number of lawsuits related to the state's responsibility for climate change damages has also increased, as these lawsuits exceed 3400 cases according to statistics from the Sabin Center for Climate Change Law. These lawsuits raise several legal problems that require the application of legal thought to determine the pillars of the state's administrative responsibility for climate change damages, the effects of this responsibility, and its specificity that imposes on the administrative judge to follow a developed approach to overcome them. Therefore, this study will focus on these problems to contribute to developing a sound concept of the state's administrative responsibility for climate change damages.